Storyboard Visualization for Gamification Design for Deaf Children's Education Using Octalysis Approach - Aisyah Ayu Mustikasari; Munawir Yusuf; Triana Rejekiningsih (Journal of International Conference Proceedings, 2022)
Deafness is a condition of deafness that makes it impossible to perceive various sound stimuli. Therefore, for the education of hearing-impaired students, it is necessary to develop special methods for the learning process, especially with regard to personality learning. In this digital age, the use of digital media and technology is a very suitable solution, especially in the field of education. The purpose of this study is digital by prioritizing visual elements in a way that hearing-impaired students can see and understand, that is, by creating gaming for hearing-impaired students. It's about developing learning media. Gamification aims to support the process of education and learning for hearing-impaired students. Gamification has a framework called octalysis. Octalysis is a tool for strategic and visual analysis of gamification. The way to design a gamification is to create a visualization in the form of a storyboard based on the gamification framework. Storyboards can be used as the basis for developing gamification, allowing you to focus more and convey the material presented. As a result, by creating a good storyboard, you can create the right gamification visualizations for hearing-impaired students to motivate them and capture the power of learning offered at school.Keywords: Deaf Student, Gamification, Octalysis, Storyboard, Education